A Comparative Study of Character Education Practices in The United States, The United Kingdom, and Indonesia - Moh Rosyid Mahmudi; Wildan Nuril Ahmad Fauzi (Balai Publikasi Indonesia, 2024)
This article discusses character education practices in the United States, the United Kingdom and Indonesia based on existing literature. Character education practices in the United States tend to use a comprehensive approach that is integrated with the academic curriculum, while the UK emphasizes the development of core values and a whole school approach. In Indonesia, character education adopts elements from both countries but shows a stronger tendency towards the US approach in some aspects. This article aims to provide a comprehensive overview of how character education practices in Indonesia compare with the US and the UK, with in-depth analyses of the key elements and practical implementation in the three countries.